Atividade antimicrobiana dos endofíticos Paenibacillus terrae e P. polymyxa em co-cultivo com Bacillus thuringiensis e B. megaterium e por adição de AgNO₃ - Barbosa, Larissa de Cassia (Universidade Federal de São Carlos, 2025)
Endophytic microorganisms, isolated from plant tissues, can provide numerous benefits to their host plants through the production of bioactive secondary metabolites. In addition to promoting plant growth and increasing resistance to biotic and abiotic stresses, these secondary metabolites have various applications, including antibiotics, insecticides, natural antioxidants, and antitumor agents. In this context, the present study aimed to evaluate the antibacterial and antifungal potential of Paenibacillus terrae and Paenibacillus polymyxa, in comparison with their co-cultivation. Both P. polymyxa and P. terrae exhibited enhanced antimicrobial activity when co-cultivated with Bacillus thuringiensis and Bacillus megaterium, achieving inhibition zones of 14, 15 and 15 mm against E. coli, S. aureus, and C. albicans, respectively. The broth microdilution test for determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) revealed antimicrobial activity only in the absence of a filtration step. Under these conditions, the most effective co-cultures reached an inhibition rate of 89%, with MIC values of 3000 µg/mL against E. coli, 6000 µg/mL against S. aureus, and 1500 µg/mL against C. albicans. The MBC values were 6000 µg/mL against both E. coli and S. aureus, and 1500 µg/mL against C. albicans. In the biosynthesis of silver nanoparticles, a positive reaction was indicated by the color change observed during the process and by characteristic peaks in UV-Vis analysis at 412, 431, and 450 nm. The average size of the synthesized nanoparticles ranged from 124 to 257 nm according to NTA, and from 140 to 566 nm according to DLS. The addition of small concentrations of nanoparticles influenced the antimicrobial activity of P. polymyxa cultures. When 8.236 × 10⁸ particles/mL were added during fermentation, the resulting inhibition zones were 15 mm, 15.33 mm, and 14.33 mm against E. coli, S. aureus, and C. albicans, respectively. These values were higher than those observed in the control, which presented inhibition zones of 11.67 mm, 13 mm, and 12.33 mm, respectively, against the same microorganisms.
Antimicrobial activity of the endophytes Paenibacillus terrae and P. polymyxa in co-culture with Bacillus thuringiensis and B. megaterium and by addition of AgNO₃
Keywords: Microrganismos endofíticos; Atividade antimicrobiana; Co-cultivo; Síntese verde; Nanopartículas metálicas; Endophytic microorganisms; Antimicrobial activity; Co-culture; Green synthesis; Metallic nanoparticles; CIENCIAS BIOLOGICAS::MICROBIOLOGIA